"Y Sin Embargo Te Quiero" (And Yet, I Love You): An Ethnographic Study of Economic Policy and Colonial Hegemonies Encoded in the Recommodification of Used Garments. (3rd July 2021) - O'Connell, Mark
Abstract: The colonial project of redistributing secondhand clothing globally can be seen fully realized in the current manifestation of the trans-global distribution of secondhand garments. In Havana however, the Clandestina brand brilliantly subverts this process. Their products are made up of old t-shirts and garments that originated in North America and Europe and were purchased cheaply through government-run Cuban stores. These are then re-cut and re-sewn into stylish shapes and silk-screened with graphics that subvert the original messages of the t-shirts. This essay examines the history of secondhand clothing as well as the current impacts of the glut of secondhand goods. It also highlights the fledgling entrepreneurial movement happening in Cuba, wherein an independent business can be operated within a trade-sector, in this case: tailoring or dressmaking. Methodology examines the sociohistorical development of the modern used clothes distribution economy, and also includes an interview with the Clandestina designers. Examining in particular how they took a commodity that was completely devalued (dumped on another marketplace), and through their ingenuity and "revolutionary vision" created a product far more valuable than the original materials. By doing so, Clandestina has created a product that is uniquely Havanero, but ready to take on the world.